2004
DOI: 10.1136/hrt.2003.016493
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic effects of oestradiol on left ventricular diastolic function in hypertensive postmenopausal women with left ventricular diastolic dysfunction

Abstract: Background: Left ventricular function changes in the postmenopausal state. However, there are conflicting reports about the effects of oestrogen on left ventricular diastolic function in postmenopausal women. Objective: To evaluate the acute and chronic effects of oestradiol in physiological doses on diastolic heart function in hypertensive postmenopausal women with left ventricular diastolic dysfunction. Methods: A prospective, randomised, double blind, placebo controlled study was used to evaluate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 31 publications
0
19
1
1
Order By: Relevance
“…Although it has been demonstrated that regular physical activity, alcohol consumption and estrogen replacement favorably alter the left ventricular relaxation 22,23 and that acute smoking causes a decrease in the E/A ratio 24,25 , we did not observe any difference regarding the frequency of these variables between the groups. However, our study did not have enough power to measure the influence of these factors on the diastolic function.…”
Section: * Data In Absolute Numbers (Percentage) -Categorical Variablcontrasting
confidence: 40%
“…Although it has been demonstrated that regular physical activity, alcohol consumption and estrogen replacement favorably alter the left ventricular relaxation 22,23 and that acute smoking causes a decrease in the E/A ratio 24,25 , we did not observe any difference regarding the frequency of these variables between the groups. However, our study did not have enough power to measure the influence of these factors on the diastolic function.…”
Section: * Data In Absolute Numbers (Percentage) -Categorical Variablcontrasting
confidence: 40%
“…In most of the studies conducted in the past few years, it has been demonstrated that the decline of cardiac structure and function could be improved by exogenous administration of estrogen alone or combined with progesterone. [20][21][22][23][24][25] Tables 1-4.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of normal calcium homeostasis with resultant calcium overload is associated with cardiac dysfunction and pathology (Katz and Reuter, 1979;Nitahara et al, 1998;Reeve et al, 2005;Yano et al, 2005). Several human studies have demonstrated that female sex hormones improve contractile performance in postmenopausal women (Alecrin et al, 2004;Fenkci et al, 2003;Sites et al, 1999;Yildirir et al, 2001). Results of some animal studies have shown that ovariectomy depresses and estrogen replacement restores myocardial performance (Schaible et al, 1984;Scheuer et al, 1987).…”
Section: Introductionmentioning
confidence: 95%